ChemInform Abstract: Cross‐Metathesis/Isomerization/Allylboration Sequence for a Diastereoselective Synthesis of anti‐Homoallylic Alcohols from Allylbenzene Derivatives and Aldehydes. Issue 15 (April 2015) - Hemelaere, Remy; Carreaux, Francois; Carboni, Bertrand
Abstract: A reaction sequence consisting of cross‐metathesis of allylarenes with vinylboronic acid, Ir‐catalyzed isomerization and allylboration to give homoallylic alcohols (IV) with excellent diastereoselectivity.